Guided osteotomy and implants placed with free hands for double full arch rehabilitation with immediate prosthetic loading - THOMÉ,Geninho (2020)
ABSTRACT Precise planning for dental implant placement requires appreciation of anatomical limitations and restorative purpose. Diagnosis can be made by complementary exams such as panoramic radiography and cone-beam computed tomography. The purpose of this study was to rehabilitate the upper and lower jaw of a patient with severe periodontal disease using a guided osteotomy and implants placed with free hands and Morse taper implants. The concept of guided surgery was used to prepare the alveolar bone to place eight implants, four implants in the upper jaw and four implants in the lower jaw, all have achieved a minimum torque of 60 Ncm. The modified suture technique was used to better stabilize the soft tissue around the mini conical abutments. The analogues were scanned by CAD/CAM for confection of the metallic structures of the bridges. On the third day, the upper and lower full arch prostheses were installed and simultaneous bilateral contacts were adjusted. After 12 months of patient follow-up, the implants and prostheses were in good condition of aesthetics and function, maintaining the success of the rehabilitation. Within the limitations of this clinical case, it can be concluded that the implants placed with free hands was facilitated by a previous guided osteotomy.